Inequality reducing taxation reconsidered - Udo Ebert (University of Oldenburg, Department of Economics, 2010)
The paper investigates inequality reducing taxation for various inequality views. Using the general definition of an inequality concept (Ebert (2004)) corresponding definitions of Lorenz dominance, inequality reduction and measures of tax progression are provided. The framework allows us to simplify and clarify the different approaches found in the literature, to extend this analysis, and to present brief and transparent proofs.
Keywords: 330